CORRELATION BETENGAN TRADITIONAL GAMES ON LOCOMOTOR MOVEMENTS AND CHARACTERS - Ika Ari Pratiwi; Mohammad Syaffruddin Kuryanto (Universitas Muria Kudus, 2019)
The purpose of this study is to determine the positive correlation between traditional games with student movements and friendly characters.The study was conducted at SD Muhammadiyah 1 Kudus. Research methods using a quantitative correlational approach. The research sample consisted of 29 students. This research technique is collecting observation data, analyzed using Pearson product-moment correlation test with prerequisite linearity and normality tests.The results showed that the data met the prerequisite test with a significance of linearity of 0.898 and the significance of normality of 0.20. Obtained results of the coefficient significance of traditional game betengan with the locomotor motion of 0.708 bigger than 0.5 and with a very strong correlation category level. On the other hand, there is a significant coefficient of correlation betengan traditional games with friendly characters of 0.702 bigger than 0.05 with a very strong level. So the results of traditional game betengan research have a strong correlation with locomotor motion and student-friendly character.